Edukasi Fisika: Pembuatan Es Krim Menggunakan Metode Contextual Teaching and Learning - Iskandar, Feri; Okimustava (LPPM ITEBA, 2025)
The low level of scientific literacy in society and the perception of physics as a difficult subject to understand pose significant challenges in enhancing public comprehension and engagement with science. Addressing these challenges requires a contextual learning approach that links physics concepts to everyday activities, enabling the community to better understand and apply scientific knowledge. This program aimed to improve public understanding of physics concepts through a contextual approach applied to ice cream-making activities, while also equipping participants with practical skills that are both educationally and economically beneficial. The activity was attended by 11 participants, mostly housewives from Mekar Sari Housing Complex, Sekupang District, Batam City. Conducted at the Posyandu facility, the program utilized the Contextual Teaching and Learning (CTL) approach, incorporating education sessions, demonstrations, hands-on ice cream making, and reflective discussions. Data collection was carried out through direct observations and Likert-scale-based pre-test and post-test questionnaires to measure participants’ understanding, skills, motivation, and creativity. The results indicated an increase in participants' understanding of physics concepts, with the average pre-test score of 58% rising to 93% in the post-test. The program also successfully enhanced participants’ motivation and creativity in applying physics concepts to everyday life. Positive feedback from participants suggested the sustainable application of the knowledge gained, particularly in home-based ice cream-making activities. This activity effectively improved participants' understanding of physics concepts, motivation, and creativity through a contextual approach based on ice cream-making, providing sustainable educational and practical benefits.